Locative prepositions “at, in, on” and translation to Vietnamese representational meaning - Tuyet Hanh, Nguyen Thi (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
Starting with the role of the reference frame under the influence of the perspective culture of the British and Vietnamese used as a cognitive premise of translation, the article presents the rationale for the procurement process on reasons, similarities, and differences in the representational meaning. The representational meaning of differences between the English locative preposition “at, in, on” and the corresponding linguistic units of Vietnamese through a particular communication context. According to the research results, when the reference object (DTQC) of the English locative position in the reference system is assimilated with the Vietnamese speaker [similar to the reference frame of the reference system], the translation semantics of the locative prepositions which is ​​"at, in, on" is like the expression representational semantics of the corresponding units in Vietnamese. The dissimilarity of the reference frames results in different structural semantics.